If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + -5m + -12 = 7m + -88 + -5 Reorder the terms: -12 + 3m + -5m = 7m + -88 + -5 Combine like terms: 3m + -5m = -2m -12 + -2m = 7m + -88 + -5 Reorder the terms: -12 + -2m = -88 + -5 + 7m Combine like terms: -88 + -5 = -93 -12 + -2m = -93 + 7m Solving -12 + -2m = -93 + 7m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-7m' to each side of the equation. -12 + -2m + -7m = -93 + 7m + -7m Combine like terms: -2m + -7m = -9m -12 + -9m = -93 + 7m + -7m Combine like terms: 7m + -7m = 0 -12 + -9m = -93 + 0 -12 + -9m = -93 Add '12' to each side of the equation. -12 + 12 + -9m = -93 + 12 Combine like terms: -12 + 12 = 0 0 + -9m = -93 + 12 -9m = -93 + 12 Combine like terms: -93 + 12 = -81 -9m = -81 Divide each side by '-9'. m = 9 Simplifying m = 9
| x-1=1# | | 4(3x-5)=5x+2(x+15) | | 2(9n-1)+7(9+6)=-60 | | 0.456=-0.3(7n-31.2) | | 4x^3+2x-28=0 | | g-9=19 | | -38=-2(-43d-24) | | 4(x-7)=2x-38 | | -10.1=w+5.3 | | 9r+22r= | | 8x+21=-59 | | 8x+21=59 | | 6x+34=4 | | 8a-3(5+2a)=85-3a | | 4a+3=2a+5 | | 33+5x=2x+75 | | 8c+1=7c-2(7+c) | | 18-4n=8-2(1+8n) | | 6X(3*5)+7(5X*3)=0 | | 6-(3*5)+7(5*3)= | | 6*(3*53)+7(5*3)= | | 6x-1=2x+6 | | 6*(3*5)+7(5*3)= | | 3m(7m+2)=0 | | 2(h+1)-2h+10= | | 5n+3+4n=16 | | 3x-7=2x-9 | | 8(x-8)=2x+8 | | -x+2x=-3 | | x+5=24 | | x+18=23 | | 26-7P=2(P-10) |